2016
DOI: 10.13075/mp.5893.00294
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating, amenorrhea, and substance use and misuse among professional ballet dancers: Preliminary analysis

Abstract: Background: Substance use and misuse (SUM), eating disorders (ED) and consequent amenorrhea (AM) occur frequently in professional ballet dancing. The objective of this study has been to explore the prevalence and association between ED, AM and SUM in ballet. Material and Methods: The sample comprised 21 ballet dancers, 23.1±4.5 years old, members of the professional National Ballet Ensemble from Croatia. Variables were collected by questionnaires examining SUM, occurrence of amenorrhea, and corresponding balle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
(35 reference statements)
1
15
0
2
Order By: Relevance
“…Research by Perić, Zenić, Sekulić, Kondrič, & Zaletel (2016) showed that, due to high volume and strenuous training, professional ballet dancers achieved a relatively high prevalence of nutritional supplementation (almost 2/3), which is in line with some other studies (Zenić, Perić, Zubcević, Ostojić, & Ostojić, 2010). It is likely that the need for supplements is greater in professional dance and full-day training and rehearsal than among amateur dancers in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Research by Perić, Zenić, Sekulić, Kondrič, & Zaletel (2016) showed that, due to high volume and strenuous training, professional ballet dancers achieved a relatively high prevalence of nutritional supplementation (almost 2/3), which is in line with some other studies (Zenić, Perić, Zubcević, Ostojić, & Ostojić, 2010). It is likely that the need for supplements is greater in professional dance and full-day training and rehearsal than among amateur dancers in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Because of this essential prerequisite, the dancers have to maintain a low-calories diet (which may significantly influence their future health, especially in the case of women) in order to achieve and maintain a desired, low body weight. These altered eating habits mainly mean a reduced consumption of particular products; this can determine a failure to provide the body with a sufficient amount of nutrients [17,18]. In addition, sometimes such diets are not prescribed by an expert and can become dangerous for health, especially when they may lead to destructive behaviors, eating disorders (anorexia, bulimia), menstrual disturbances and low bone mineral density [19].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of smoking is regularly lower in adolescents who practice sports, but some groups of athletes (e.g., adolescents involved in sports where a lean body figure is an important determinant of success, females, and adolescents who quit sports) were found to be at risk of smoking [24,25]. In addition, in some regions where smoking is prevalent and socially accepted, no specific influence of sports participation on smoking prevalence in adolescents was observed [8,26,27].…”
Section: Introductionmentioning
confidence: 98%
“…In brief, participation in team sports was repeatedly associated with higher likelihood of alcohol drinking (because of the post-sport social gatherings) [32]. On the other hand, athletes involved in some individual sports were often at risk of smoking (i.e., in some aesthetic sports athletes are concerned on body weight, because smoking increases basal metabolism) [24,25]. Other facets of sports participation that are found as being specifically related to substance misuse in puberty include experience, level of sport competition (i.e., sport achievement), and intensity of training (i.e., commitment to sport), altogether highlighting the necessity for more profound studying of the problem [7,27,31].…”
Section: Introductionmentioning
confidence: 99%